Consumers' Perception of Urban Farming—An Exploratory Study - Grebitus, Carola; Chenarides, Lauren; Muenich, Rebecca; Mahalov, Alex (Frontiers in Sustainable Food Systems, 2020)
Urban agriculture offers the opportunity to provide fresh, local food to urban communities. However, urban agriculture can only be successfully embedded in urban areas if consumers perceive urban farming positively and accept urban farms in their community. Success of urban agriculture is rooted in positive perception of those living close by, and the perception strongly affects acceptance of farming within individuals’ direct proximity. This research investigates perception and acceptance of urban agriculture by means of a qualitative, exploratory field study with N=19 residents from a major metropolitan area in the southwest U.S. Specifically, the concept mapping procedure was used, where respondents are free to write down all the associations that come to mind when presented with a stimulus, such as, “urban farming.” When applying concept mapping, participants are asked to recall associations and then directly link them to each other displaying their knowledge structure, i.e., perception. Data were analyzed using content analysis and semantic network analysis. Consumers’ perception of urban farming is related to the following categories: environment, society, economy, and food and attributes. The number of positive associations is much higher than the number of negative associations signaling that consumers would be likely to accept farming in close proximity to where they live. Furthermore, our findings show that individuals’ perceptions can differ greatly in terms of what they associate with urban farming and how they evaluate it. While some only think of a few things, others have well-developed knowledge structures. Overall, investigating consumers’ perception helps designing strategies towards developing successful urban farming.